1996
DOI: 10.1104/pp.110.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Oleosins and Oil Bodies in Seeds and Other Organs

Abstract: Diverse organisms store lipids in subcellular particles as food reserves, which will be mobilized during a forthcoming period of active metabolism. These lipid particles can be found in the seeds, pollens, flowers, roots, and stems of flowering plants, the spores and vegetative organs of nonflowering plants, and algae. They are also present in some animal cells, fungi, and Euglena. Of a11 these subcellular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
363
0
17

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(389 citation statements)
references
References 16 publications
9
363
0
17
Order By: Relevance
“…The acyl chains of the phospholipid monolayer are embedded in the TAG interior of the oil body. Oleosin is a structural protein that is thought to prevent coalescence of oil bodies during seed dehydration (Huang, 1996). That oil bodies originate from the endoplasmic reticulum is consistent with the finding that enzymes of TAG synthesis, including DGAT, are present in microsomal membrane fractions, which are known to contain vesicles of endoplasmic reticulum (Kwanyuen and Wilson, 1986).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The acyl chains of the phospholipid monolayer are embedded in the TAG interior of the oil body. Oleosin is a structural protein that is thought to prevent coalescence of oil bodies during seed dehydration (Huang, 1996). That oil bodies originate from the endoplasmic reticulum is consistent with the finding that enzymes of TAG synthesis, including DGAT, are present in microsomal membrane fractions, which are known to contain vesicles of endoplasmic reticulum (Kwanyuen and Wilson, 1986).…”
supporting
confidence: 63%
“…Not only do they both store TAG, but plastoglobuli also appear to be coated with a structural protein termed fibrillin or plastid lipidassociated-protein, which is analogous to oil body oleosin (Pozueta-Romero et al, 1997;Kessler et al, 1999;Rey et al, 2000). Fibrillin and oleosin are thought to prevent coalescence of plastoglobuli and oil bodies, respectively (Huang, 1996;Rey et al, 2000). Moreover, recent experiments with transgenic plants in which fibrillin was overexpressed have indicated that the availability of fibrillin regulates the formation of plastoglobuli in much the same way that oleosin regulates the formation of oil bodies (Huang, 1992;Rey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of bands also occur at less than 29 kDa, probably corresponding to oleosins (HUANG, 1996). Bands can also be seen at less than 14.4 kDa.…”
Section: Sds-polyacrylamide Gel Electrophoresis (Sds-page)mentioning
confidence: 87%
“…2 and 7), we captured in type I infructescences stages prior to and at the onset of seed germinability until full premature germination (prior to dormancy induction), and in types II and III infructescences we captured all stages prior to, during, and after the induction of primary dormancy, including the full premature germination stage. To assign these stages to events during seed development and maturation on the molecular level, we analyzed the expression patterns of well-known marker proteins including oleosin (seed storage accumulation), EM6 (seed maturation), and dehydrin (desiccation tolerance; Close et al, 1993;Huang, 1996;Bies et al, 1998;Crowe et al, 2000;Ruuska et al, 2002;Boudet et al, 2006;Siloto et al, 2006;Leprince and Buitink, 2010). Oleosin accumulation during L. papillosum seed development was enhanced with the onset of premature germinability and early maturation in type I and II infructescences.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%